Business failures and problems in Malaysia / Law Kuan Kheng and Wan Irham Ishak - Law, Kuan Kheng; Ishak, Wan Irham (Faculty of Business & Management, Universiti Teknologi MARA (UiTM) Cawangan Kedah, 2021)
Entrepreneurship has become a common issue to be discussed by many people today. Curran and Stanworth (1989) perceived entrepreneurship as a process of creating something new in the market while Low and MacMillan (1988) defined it as the set up a new business. To start a new business is not an easy task. As an entrepreneur, they need to face a lot of challenges. To be successful in the business, the entrepreneur needs to possess characteristic of risk- taking ability, need for achievement, locus of control, desire for autonomy, deviancy, creativity and opportunism (Kirby, 2004).